2014
DOI: 10.1111/desc.12258
|View full text |Cite
|
Sign up to set email alerts
|

The late positive potential predicts emotion regulation strategy use in school‐aged children concurrently and two years later

Abstract: The ability to use cognitive emotion regulation strategies such as reappraisal may be a core component of emotional competence across development, but due to methodological challenges in measuring such strategies, they are rarely studied in young children. One neurophysiological measure, the late positive potential (LPP) has been examined in response to reappraisal as a potential neurosignature for emotion regulatory capacity in adults. The association between the LPP and emotion regulatory capacity in childre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
35
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 37 publications
1
35
0
Order By: Relevance
“…Limited research has examined the LPP in children and adolescents, but it has been established in children as young as 5 years (Dennis & Hajcak, ) and can be modulated by effective use of emotion regulation strategies (like reappraisal—thinking differently about one's emotions to reduce their intensity). For example, Babkirk, Rios, and Dennis () showed that modulation of the LPP predicts emotion regulation strategy use in school‐aged children, indicating that this ERP may be a neural marker of adaptive emotional development. The emotion regulation strategies children used during disappointing and frustrating laboratory tasks were observed, and the children who showed more reappraisal‐related modulation of the LPP at age 5 were using more adaptive strategies to manage their disappointed and frustrated feelings both concurrently and 2 years later.…”
Section: Neurophysiological Approaches To Understanding Emotion Reactmentioning
confidence: 99%
See 1 more Smart Citation
“…Limited research has examined the LPP in children and adolescents, but it has been established in children as young as 5 years (Dennis & Hajcak, ) and can be modulated by effective use of emotion regulation strategies (like reappraisal—thinking differently about one's emotions to reduce their intensity). For example, Babkirk, Rios, and Dennis () showed that modulation of the LPP predicts emotion regulation strategy use in school‐aged children, indicating that this ERP may be a neural marker of adaptive emotional development. The emotion regulation strategies children used during disappointing and frustrating laboratory tasks were observed, and the children who showed more reappraisal‐related modulation of the LPP at age 5 were using more adaptive strategies to manage their disappointed and frustrated feelings both concurrently and 2 years later.…”
Section: Neurophysiological Approaches To Understanding Emotion Reactmentioning
confidence: 99%
“…Most of this work has focused on cognitive reappraisal, a strategy that involves reframing or thinking differently about a stimulus to change one's feelings. Though children can use and describe cognitive strategies like reappraisal from as young as 5–6 years (e.g., Babkirk et al, ; Davis, Levine, Lench, & Quas, ; Dennis & Hajcak, ), the ability to use them well continues to develop throughout childhood and adolescence (Dougherty, Blankenship, Spechler, Padmala, & Pessoa, ; McRae et al, ; Silvers et al, ). fMRI studies of emotion regulation strategy use have provided evidence of age‐related changes in lateral prefrontal cortex (LPFC) recruitment (McRae et al, ), amygdala modulation (Pitskel, Bolling, Kaiser, Crowley, & Pelphrey, ), and more recently, the integration of these two components in the ventrolateral PFC‐amygdala pathway hypothesis set forth by Silvers and colleagues (Belden, Luby, Pagliaccio, & Barch, ; Silvers et al, , ).…”
Section: Neurophysiological Approaches To Understanding Emotion Reactmentioning
confidence: 99%
“…Finally, the LPP, which usually follows the P300 response and occurs around 500-1,000 ms, is implicated in elaborative evaluation of valenced (positive or negative) material in both adults (Hajcak, MacNamara, & Olvet, 2010) and children (DeCicco, Solomon, & Dennis, 2012). Like the P300, the LPP can be modulated by cognitive control and is sensitive to task demands (Hajcak, Moser, & Simons, 2006), can reflect appraisal strategies (Babkirk, Rios, & Dennis, 2015), and is strongest to affective over neutral stimuli (Cuthbert, Schupp, Bradley, Birbaumer, & Lang, 2000). In examining the full neural time course-early (EPN or P2), middle (P3), and late (LPP) components, we can examine the extent to which distributive justice evaluations and decisions are made in response to automatic, visceral neural responses, or deliberate and controlled ones.…”
mentioning
confidence: 99%
“…The LPP has been used extensively as a measure of emotional face processing among adults, and of late, the LPP has been found to be reliably elicited in children (Kujawa, Klein, & Proudfit, 2013; see also Babkirk, Rios, & Dennis, 2014; DeCicco, O'Toole, & Dennis, 2014; Dennis & Hajcak, 2009; Hajcak & Dennis, 2009; Solomon, DeCicco, & Dennis, 2012). Recent work has also sought to characterize age-related changes in the LPP using cross-sectional and longitudinal approaches.…”
mentioning
confidence: 99%